Photosensitive Layer-by-Layer Assemblies Containing Azobenzene Groups: Synthesis and Biomedical Applications - Akiba, Uichi (Polymers (Basel), 2017)
This review provides an overview of the syntheses of photosensitive layer-by-layer (LbL) films and microcapsules modified with azobenzene derivatives and their biomedical applications. Photosensitive LbL films and microcapsules can be prepared by alternate deposition of azobenzene-bearing polymers and counter polymers on the surface of flat substrates and microparticles, respectively. Azobenzene residues in the films and microcapsules exhibit trans-to-cis photoisomerization under UV light, which causes changes in the physical or chemical properties of the LbL assemblies. Therefore, azobenzene-functionalized LbL films and microcapsules have been used for the construction of photosensitive biomedical devices. For instance, cell adhesion on the surface of a solid can be controlled by UV light irradiation by coating the surface with azobenzene-containing LbL films. In another example, the ion permeability of porous materials coated with LbL films can be regulated by UV light irradiation. Furthermore, azobenzene-containing LbL films and microcapsules have been used as carriers for drug delivery systems sensitive to light. UV light irradiation triggers permeability changes in the LbL films and/or decomposition of the microcapsules, which results in the release of encapsulated drugs and proteins.